DEVELOPMENT OF MARKETING STRATEGY THROUGH SOCIAL MEDIA IMPACT ON CONSUMER BEHAVIOR IN THE DIGITAL ERA - Widyatmoko Widyatmoko (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this research is to find out new activities regarding consumer behavior attitudes to make a purchase decision due to the marketing strategy that applies in the digital era. For the research method using a study through library research. With a literature review, it can describe and explain that the digital era is proven to be able to influence all areas of life, including the business world. The digital era has produced renewable and up-to-date ideas for consumers or marketers or also for other users. Marketing strategies that are always developing can influence consumer behavior because they are starting to switch habits in shopping online through platforms on social media. The results of this study indicate that marketing strategies through social media have caused a shift in consumer attitudes and behavior from conventional or traditional activities to activities using digital or online technology. Marketers are required to adapt to changes in consumer behavior which is the key to success in being able to maintain the viability of the company through marketing strategies according to the era and changes in consumers. The ability of marketers or companies to be able to always understand consumer behavior is a strategy that is needed and considered because it is something that needs attention to achieve competitive advantage. By carrying out a marketing strategy that uses digital information technology devices, it will be easy to provide opportunities for consumers to find information about the products they will buy as well as testimonials from other consumers about consumer experiences after experiencing the benefits and success of consuming a particular product.